Analisis Kebijakan Pemerintah Kabupaten Ponorogo Tentang Program Kegiatan Rukun Tetangga - Prastiyo, Danang; Widiyahseno, Bambang; Ridho, Irvan Nur; Hilman, Yusuf Adam (Jurnal Pallangga Praja (JPP), 2023)
Ponorogo Regency launched an assistance program for community strengthening in the smallest scope, namely the Rukun Tetangga (RT). ratified through Circular Letter (SE) of the Regent. The Ponorogo Regency Government provides funds of IDR 10,000,000 annually to each Neighborhood Association in the entire Ponorogo Regency Region which consists of 6,869 the Rukun Tetangga (RT). The programs include: making infiltration wells or what is called Biopori Infiltration, Waste Management in the RT scope, provision of RT Wireless Fidelity (Wifi) networks, Strengthening Women's Economy, Employment BPJS benefits and incentives for RT administrators, Family Medicine Planting and Resident; Rembug Warga. This study aims to find out how the program is implemented and what are the obstacles. This type of research uses a descriptive method with a qualitative approach. The results of this study show that this RT activity program is an initiation from the Regent of Ponorogo which has been stated in the vision and mission. All RT activity programs have been implemented, but there are several programs that are not appropriate because they are not in accordance with regional conditions, such as: Biopore Infiltration, Integrated Waste, and planting family medicine. programs that are not suitable because they do not involve the RT community who know their needs better.